Nuclear lipidome is altered in amyotrophic lateral sclerosis: A pilot study. Issue 2 (12th May 2021) - Ramírez‐Nuñez, Omar; Jové, Mariona; Torres, Pascual; Sol, Joaquim; Fontdevila, Laia; Romero‐Guevara, Ricardo; Andrés‐Benito, Pol; Ayala, Victòria; Rossi, Chiara; Boada, Jordi; Povedano, Mònica; Ferrer, Isidro; et al.
Abstract: Nucleocytosolic transport, a membrane process, is impaired in motor neurons in amyotrophic lateral sclerosis (ALS). This study analyzes the nuclear lipidome in motor neurons in ALS and examines molecular pathways linked to the major lipid alterations. Nuclei were obtained from the frozen anterior horn of the lumbar spinal cord of ALS patients and age‐matched controls. Lipidomic profiles of this subcellular fraction were obtained using liquid chromatography and mass spectrometry. We validated the mechanisms behind presumable lipidomic changes by exploring ALS surrogate models including human motor neurons (derived from ALS lines and controls) subjected to oxidative stress, the h SOD‐G93A transgenic mice, and samples from an independent cohort of ALS patients. Among the differential lipid species, we noted 41 potential identities, mostly belonging to phospholipids (particularly ether phospholipids, as plasmalogens), as well as diacylglycerols and triacylglycerides. Decreased expression of alkyldihydroxyacetonephosphate synthase ( AGPS )—a critical peroxisomal enzyme in plasmalogen synthesis—is found in motor neuron disease models; this occurs in parallel with an increase in the expression of sterol carrier protein 2 ( SCP2 ) mRNA in ALS and Scp2 levels in G93A transgenic mice. Further, we identified diminished expression of diacylglycerol‐related enzymes, such as phospholipase C βI ( PLCβI ) and protein kinase CβII ( PKCβII ), linked to diacylglycerol metabolism. Finally, lipid droplets were recognized in the nuclei, supporting the identification of triacylglycerides as differential lipids. Our results point to the potentially pathogenic role of altered composition of nuclear membrane lipids and lipids in the nucleoplasm in the anterior horn of the spinal cord in ALS. Overall, these data support the usefulness of subcellular lipidomics applied to neurodegenerative diseases. Abstract : Lipidomic analyses of nuclear enriched fractions obtained from frozen tissue samples reveals amyotrophic lateral sclerosis (ALS) linked changes in nuclear lipid components. We show altered contents of ether lipid, diacylglyceride (DAG) and triacylglyceride (TAG) in nuclear fractions. These changes can be related to specific enzymes governing lipid composition, such as peroxisomal enzymes and DAG‐related ones. ​